Bài 1:Tìm số nguyên x , biết : 1) 5x-(-25)=35 2) -6x – 14= -44 3) 95-105 : x=60 7) 21-(29+4x)= -12 9) -14 – 5 . (30-x)=26 10) 2x + 5 = -3 11) 12-3x=

Question

Bài 1:Tìm số nguyên x , biết :
1) 5x-(-25)=35
2) -6x – 14= -44
3) 95-105 : x=60
7) 21-(29+4x)= -12
9) -14 – 5 . (30-x)=26
10) 2x + 5 = -3
11) 12-3x= -30
12) 461+(x-45)=387
13) 15-(3-x)=(-10)

in progress 0
Lydia 1 năm 2021-10-09T02:40:35+00:00 2 Answers 7 views 0

Answers ( )

    0
    2021-10-09T02:41:43+00:00

    Đáp án: 1) x=2 

                 2) x=5

                 3) x=3

                 7) x=1

                 9) x=38

                 10) x= -4

                 11) x=14

                 12) x= -29

                 13) x=-22

    Giải thích các bước giải:

    Bài 1:Tìm số nguyên x , biết :

    1) 5x-(-25)=35 

    => 5x+25=35

    => 5x=35-25

    => 5x=10

    => x=2

    2) -6x – 14= -44

    => -6x=-44+14

    => -6x=-30

    => x=5

    3) 95-105 : x=60

    => 105:x=95-60

    => 105:x=35

    => x=3

    7) 21-(29+4x)= -12

    => 29+4x=21+12

    => 29+4x=33

    => 4x=33-29

    => 4x=4

    => x=1

    9) -14 – 5 . (30-x)=26

    => 5(30-x)=-14-26

    => 5(30-x)=-40

    => 30-x=-8

    => x=38

    10) 2x + 5 = -3

    => 2x=-3-5

    => 2x=-8

    => x=-4

    11) 12-3x= -30

    => 3x=12+30

    => 3x=42

    =>  x= 14

    12) 461+(x-45)=387

    => x-45=387-461

    => x-45= -74

    => x=-74 +45

    => x=-29

    13) 15-(3-x)=(-10)

    => 3-x=15+10

    => 3-x =25

    => x=-22

    Em tham khảo nhé!

    0
    2021-10-09T02:42:03+00:00

    Đáp án:

    Giải thích các bước giải:

    `1) 5x-(-25)=35`

    `->5x+25=35`

    `->5x=35-25`

    `->5x=10`

    `->x=2`

    Vậy `x=2`

    `2) -6x – 14= -44`

    `->-6x=-44+14`

    `->-6x=-30`

    `->x=5`

    Vậy `x=5`

    `3)95-105 : x=60`

    `->105:x=95-60`

    `->105:x=35`

    `->x=105:35`

    `->x=3`

    Vậy `x=3`

    `7) 21-(29+4x)= -12`

    `->21-29-4x=-12`

    `->-8-4x=-12`

    `->4x=-8-(-12)`

    `->4x=4`

    `->x=1`

    Vậy `x=1`

    `9) -14 – 5 (30-x)=26`

    `->5(30-x)=-14-26`

    `->150-5x=-40`

    `->5x=150-(-40)`

    `->5x=190`

    `->x=38`

    Vậy `x=38`

    `10)2x + 5 = -3`

    `->2x=-3-5`

    `->2x=-8`

    `->x=-4`

    Vậy `x=-4`

    `11) 12-3x= -30`

    `->3x=12-(-30)`

    `->3x=42`

    `->x=14`

    Vậy `x=14`

    `12) 461+(x-45)=387`

    `->461+x-45=387`

    `->416+x=387`

    `->x=387-416`

    `->x=-29`

    Vậy `x=-29`

    `13) 15-(3-x)=(-10)`

    `->15-3+x=-10`

    `->12+x=-10`

    `->x=-10-12`

    `->x=-22`

    Vậy `x=-22`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )